(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The St. Martin’s Island, the only offshore coral island in Bangladesh depends on solely groundwater for domestic uses. This study finds that groundwater occurs between 1m and 7m depths within four different aquifer lobes distributed throughout the island. These lobes are formed by deposition of beach sands within bedrock depression and are completely isolated from the influence of sea water. The model simulated groundwater budget for one of the lobes suggests that 11% of total dynamic reserve is used for water supply to local inhabitants and seasonal tourists and the rest is lost due to evapotranspiration and seepage along the boundary of the aquifer. The chemically suitable quality of potable groundwater prevails throughout the island but presence of Escherichia coli in the groundwater samples of the island possesses a great health threat. E. coli is found in 58% and 44% of the groundwater samples during dry and wet season, respectively. The unplanned construction of resorts and their septic tanks within the aquifer are responsible for the pathogenic contamination of groundwater in the St. Martin’s Island. Although currently there is no threat of seawater intrusion, the rise of sea level over the bedrock barrier and storm surge inundation may destroy this resource in near future. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 63-72